2004
DOI: 10.1086/426542
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry in the Changing Jets of SS 433 and Its True Distance from Us

Abstract: We present the deepest yet radio image of the Galactic jet source, SS 433, which reveals over two full precession cycles (> 2 × 163 days) of the jet axis. Systematic and identifiable deviations from the traditional kinematical model for the jets are found: variations in jet speed, lasting for as long as tens of days, are necessary to match the detailed structure of each jet. It is remarkable that these variations are equal and opposite, matching the two jets simultaneously. This explains certain features of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
154
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(168 citation statements)
references
References 12 publications
11
154
0
Order By: Relevance
“…W50 is an extended SNR located at about 5.5 kpc (Blundell & Bowler 2004;Lockman et al 2007). It consists of a central component with a diameter of about 1 • and two "ears" extended to the northwest and southeast (see Fig.…”
Section: G397−20 (W50)mentioning
confidence: 99%
“…W50 is an extended SNR located at about 5.5 kpc (Blundell & Bowler 2004;Lockman et al 2007). It consists of a central component with a diameter of about 1 • and two "ears" extended to the northwest and southeast (see Fig.…”
Section: G397−20 (W50)mentioning
confidence: 99%
“…jets on a scale of several arcseconds) is larger than the distance determined by the kinematics of the inner jets (i.e. jets on a sub-arcsecond scale): 5.5 ± 0.2 kpc (Hjellming & Johnston, 1981;Blundell & Bowler, 2004) from images unresolved in time of the extended jets vs. the estimates 4.9 ± 0.2 kpc (Spencer, 1984), 4.85 ± 0.2 kpc (Vermeulen et al, 1993) and 4.61 ± 0.35 kpc (Stirling et al, 2002) from proper motion of radio knots in the inner jets, and 5.0 ± 0.3 kpc (Fejes, 1986) and 5.0 ± 0.5 kpc (Romney et al, 1987) from images unresolved in time of the inner jets. This dichotomy might be explained by the fact that an a priori assumption of constancy of the jet velocity in kinematic simulations of really decelerating jets leads to an overestimate of the distance to SS 433, D, so that the model jet matches the observed angular jet size, which is proportional in the first approximation to the ratio v j /D.…”
Section: Introductionmentioning
confidence: 98%
“…Though the radio jets at their origin are intimately connected with the optical jets, which are believed to be ballistic (Kopylov et al, 1987), their behaviour differs slightly: the radio jets deviate from the kinematics of the optical jets by more than 10% (e.g. Blundell & Bowler, 2004;Schillemat et al, 2004;Roberts et al, 2008); the radio clouds can be found far away from the jets (e.g. Spencer, 1984;Romney et al, 1987); the radio jets appear to be more continuous (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The distance of SS 433 has also remained uncertain for a long time. From complete observations of the radio emitting materials ejected in the relativistic jets and after taking the kinematic model into account, Blundell & Bowler (2004) eventually determined this distance as d = 5.5 ± 0.2 kpc.…”
Section: Introductionmentioning
confidence: 99%